Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 4378 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Spartina anglica C.E.Hubb." ] } The dataset includes 4378 records from 78 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006991-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences